Prediction Scores Do Not Correlate with Clinically Adjudicated Categories of Pulmonary Embolism in Critically Ill Patients - CM Katsios; M Donadini; M Meade; S Mehta; R Hall; J Granton; J Kutsiogiannis; P Dodek; D Heels-Ansdell; L McIntyre; N Vlahakis; J Muscedere; et al. (Canadian Respiratory Journal)
BACKGROUND: Prediction scores for pretest probability of pulmonary embolism (PE) validated in outpatient settings are occasionally used in the intensive care unit (ICU).